Efektivitas Berbagai Media Saring untuk Menurunkan Kesadahan di Desa Kalisari Kecamatan Rowokele Kabupaten Kebumen - Ari Rahmawati; Narto Narto; Haryono Haryono (Sanitasi: Jurnal Kesehatan Lingkungan, 2018)
Water is an environmental component that has prominent role for life. Based on the regulationissued by MoH No.416/ Menkes/Per/IIX/1990 about Requirements and Control of Clean WaterQuality, one of the chemical criterions is no chemical CaCO3 or water hardness. Hard water cancause renal impairment due to accumulation of CaCO3 and MgCO3 deposits inside human body.Ketapang leaf, chinese teak leaf and papaya root are example of the plants that contain naturalresin compounds that can be used as a reducer for water hardness.The purpose of this studywas to determine the decrease of hardness level after the water were treated by applying thosevarious filter media, by conducting true experiment with pre-test post-test with control group design. The study site was in Kalisari Village of Rowokele District of Kebumen Regency. The fivetreatment groups under study were: filtration A (ketapang leaves), filtration B (chinese teak leaves), filtration C (papaya roots, filtration D (resin zeolite), and filtration E (without filter media) ascontrol. There were five replications. The controlled confounding variables were: season, flowdischarge, contact time and faucet outlet. Analysis result by using one way anova test gained ap-value <0,001; which means that, statistically, the hardness yielded by filtration treatment ofvarious media types is significant-ly different. The subsequent LSD test shows that the mosteffective filtration media is papaya roots, and followed by resin zeolit, chinese teak leaves, ketapang leaves, and the control.